Trends of Transmitted and Acquired Drug Resistance in Europe From 1981 to 2019 - Miranda, Mafalda N.S. (2022)
Funding Information: We want to thank Frank Tang, Bin Lin, Mike Cohen and the rest of the Google speech team for their insightful discussions and inputs. Publisher Copyright: Copyright © 2022 Miranda, Pingarilho, Pimentel, Martins, Kaiser, Seguin-Devaux, Paredes, Zazzi, Incardona and Abecasis.